INOVASI PROGRAM PELAYANAN THREE IN ONE DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA BANDAR LAMPUNG - Lies Kumara Dewi (Universitas Bandar Lampung (UBL), 2022)
One of the service innovations carried out by the Population and Civil Registration Office of Bandar Lampung City is the Three In One Service which is provided by the Civil Service Office to residents who request by submitting 1 (one) file to get 3 (three) documents. Example Application for a newborn child is entered into the family card as well as getting a birth certificate and child's identity card. This research will see what innovation service for the wider community the Three in One service program at the Department of Population and Civil Registration of Bandar Lampung City. In conducting this research, the method used is, qualitative descriptive., descriptive method is defined as a problem solving procedure investigated by describing or describing the current state of the subject or object of research (a person, institution, community, etc.) based on the facts that appear or are what they are. In describing the research, the data collected is data in the form of documentation and also conducting interviews and also conducting observations. Things that will be shown from this research are in the form of that the three-in-one public service innovation has been running well but not yet optimal. Aspects that become obstacles to the three in one service innovation inhibiting factors include the accumulation of service applicant files and the length of the three in one application file completion process, namely KK, KIA and Birth Certificates